Ketanserin improves cardiac performance after myocardial infarction in spontaneously hypertensive rats partially through restoration of baroreflex function - Yu Jian-guang; Zhang En-hui; Liu Ai-jun; Liu Jian-guo; Cai Guo-jun; Su Ding-feng (Acta Pharmacologica Sinica, 2016)
Aim: Baroreflex dysfunction is associated with a higher rate of sudden death after myocardial infarction (MI). Ketanserin enhances baroreflex function in rats. The present work was designed to examine whether ketanserin improves the post-MI cardiac function and to explore the possible mechanism involved. Methods: Spontaneously hypertensive rats (SHR) were treated with ketanserin (0.3 mg·kg−1·d−1). Two weeks later, blood pressure and baroreflex function were measured, followed by a ligation of the left coronary artery. The expressions of vesicular acetylcholine transporter (VAChT) and α7 nicotinic acetylcholine receptor (α7-nAChR) in ischemic myocardium, angiogenesis, cardiac function, and left ventricular (LV) remodeling were evaluated subsequently. Results: Ketanserin significantly improved baroreflex sensitivity (0.62±0.21 vs 0.34±0.12 ms/mmHg, P